Pathological stage distribution in patients treated with radical prostatectomy reflecting the need for protocol-based active surveillance: results from a contemporary European patient cohort - Seiler, Daniel; Randazzo, Marco; Grobholz, Rainer (BJU international, 2012)
Study Type - Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Low-risk prostate cancer is frequently diagnosed in the context of PSA screening or during a routine check-up. For those patients, to avoid possible overtreatment AS is an increasingly chosen treatment option. However, the concept of AS could possibly misclassify potentially dangerous PCa as a low-risk disease resulting in inferior cancer control outcomes. In the present study, we could demonstrate that the histopathological results of patients treated by RP in course of AS are significantly better if the selection criteria for AS are entirely fulfilled. Our findings underline the importance of a strict and precise admittance procedure for patients with early prostate cancer who are willing to undergo an AS programme. OBJECTIVE • To compare the histopathological outcomes of patients treated with radical prostatectomy (RP) after an initial active surveillance (AS) for localized, low-risk prostate cancers (PCa) among men who fulfilled the Epstein criteria at diagnosis with those who did not. PATIENTS AND METHODS • In all, 283 patients with localized PCa were initially managed at our institution with AS. • In all, ≈50% originated from the European Randomized Study of Screening for Prostate Cancer (ERSPC) participants from Switzerland: 75 (26.5%) patients underwent treatment during follow-up and 61 were treated with RP (21.6%). • These patients were stratified into those who did (n= 39) vs those who did not (n= 22) entirely fulfil AS inclusion criteria according to Epstein et al. at PCa diagnosis. RESULTS • Patients who did completely fulfil the AS inclusion criteria had significantly lower prostate-specific antigen (PSA)-values (4.9 vs 7.8 ng/mL; P= 0.02), a significantly lower PSA density at diagnosis (0.09 vs 0.2 ng/mL/ccm; P= 0.007) and at RP, a higher proportion of organ-confined cancers (89.7% vs 59.1%, P= 0.02) and fewer positive surgical margins (25.6% vs 40.9%). • However, the rate of favourable histopathological outcome, defined as organ-confined disease with negative surgical margins, was statistically significantly higher in the group fulfilling AS criteria (69.2% vs 40.9%; P= 0.03). CONCLUSIONS • In our AS series, 26.5% of the patients underwent definitive therapy. • Most patients treated with RP had organ-confined disease in the majority of cases, especially when the Epstein criteria were rigorously fulfilled at PCa diagnosis. • This underlines the importance of a strict and precise per protocol AS for patients with early PCa, otherwise there is a risk of missing more significant disease.